2022
DOI: 10.30865/mib.v6i4.4639
|View full text |Cite
|
Sign up to set email alerts
|

Application of Data Mining using Naive Bayes for Student Success Rates in Learning

Abstract: Education is a very important part of human life because through education quality human resources will be formed. Quality education can be read and measured by the achievement of various indicators. However, achieving these indicators is not easy, because learning success is influenced by several factors. One of the factors that can affect the success of learning is the learning system. To understand the level of student success in learning, a data mining processing technique is needed. The algorithm that wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Gaussian Naive Bayes, a probabilistic classifier underpinned by Bayes' Theorem, is a pivotal tool in the predictive analytics arsenal, particularly in the educational sector [12]. This algorithm stands out for its application of Gaussian probability distribution to handle continuous data, a common characteristic in educational datasets.…”
Section: Gaussian Naive Bayesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian Naive Bayes, a probabilistic classifier underpinned by Bayes' Theorem, is a pivotal tool in the predictive analytics arsenal, particularly in the educational sector [12]. This algorithm stands out for its application of Gaussian probability distribution to handle continuous data, a common characteristic in educational datasets.…”
Section: Gaussian Naive Bayesmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of Gaussian Naive Bayes in educational data analysis. Wijaya et al [12] applied the Naive Bayes algorithm to predict student success rates in learning, achieving high accuracy. Ouissal Sadouni and Abdelhafid Zitouni [13] discusses the implementation of dynamic optimization of learning indicators using Naive Bayes Classifier, which is relevant to understanding the application of Gaussian Naive Bayes in educational settings.…”
Section: Gaussian Naive Bayesmentioning
confidence: 99%